A self-assembled nanopatch with peptide–organic multilayers and mechanical properties1. Issue 6 (14th February 2015) - Liu, Lei; Li, Yibao; Xia, Dan; Bortolini, Christian; Zhang, Shuai; Yang, Yanlian; Pedersen, Jan S.; Wang, Chen; Besenbacher, Flemming; Dong, Mingdong
<x xml:space="preserve">Abstract</x> The organic molecule tuning could enable peptides to self-assemble into nanopatch structure.